Addressing Workplace Violence Against Transgender Individuals Ensuring Inclusive And Safe Environments - Arslan, Muhammad Qasim; Fatima, Urooj; Rafia, Syeda (Annals of Human and Social Sciences, 2023)
This paper investigates workplace violence against transgender people in Pakistan through an extensive literature review and large-scale empirical study. The background outlines the discrimination and marginalization transgender individuals face in society and employment. Workplaces are rife with bullying, harassment, and assault which negatively impacts job performance, satisfaction, and mental health. Barriers to justice include police mistreatment and lack of legal protections for transgender victims. A survey of 250 transgender respondents reveals shockingly high rates of unchecked sexual (70%), physical (60%), and psychological (80%) abuse over the past year. Most victims do not report violence due to indifference and harassment from authorities. Abuse causes severe depression, anxiety, trauma, and suicidal ideation. The data shows differences in violence rates by region, age, and socioeconomic status. There is an urgent need for legal reform to prohibit discrimination, increased police training and accountability, government-funded mental health services, coalitions between advocacy groups, and public education campaigns to address this systemic human rights crisis. The paper provides concrete policy recommendations based on the data to alleviate suffering and ensure transgender individuals in Pakistan have their basic rights upheld.